Prevalence and molecular characterization of some circulating strains of the peste-des-petits-ruminants virus in Saudi Arabia between 2014–2016 - Hemida,Maged Gomaa; Alghadeer,Hussain Mohammed; Alhammadi,Mohammed; Ali,Sayed (PeerJ, 2020)
Background The peste-des-petits-ruminants virus (PPRV) is a highly devastating virus of small ruminants in many parts of the world, including the Kingdome of Saudi Arabia. Therefore, our objectives were (1) to conduct a molecular prevalence study of PPRV in sheep and goat across the KSA and (2) to isolate and identify currently circulating PPRV lineages. Swabs and tissue specimens were collected from 97 herds suspected to be infected with PPRV across the Kingdome of Saudi Arabia (KSA). Testing for the presence of the virus was done by the real-time PCR. Confirmation of the identity of the reactions was done by the gel-based-PCR then by sequencing of the partial PPRV genome. Results Our results revealed that 24.1% of the tested specimens were PPRV-positive. Isolation of PPRV was successful from samples using the Vero cell line. Sequence analysis of some partial PPRV genes (N, F, M, L, P, and H) revealed that these strains were belonging to lineage IV of the PPRV. Conclusions This is the first study to conduct both the nationwide prevalence, isolation, and molecular characterizations of the PPRV in the KSA. Continuous surveillance and monitoring of the circulating strains of PPRV among sheep and goats will contribute substantially to the global eradication campaign of such a virus.
Keywords: SRMV; ELISA; PCR; Real Time PCR; Small ruminants; lineage IV; Saudi Arabia